Property Market Analysis of the Hospitality Sector in Central Lombok District - Doni Triono; Saefuddin Baharsyah (CV. Syntax Corporation Indonesia, 2023)
The number of tourists visiting and the number of hotel rooms available in Central Lombok Regency are growing in line with the development of tourism in Central Lombok Regency. To estimate the need for the number of hotel rooms in Central Lombok Regency, it is necessary to research the property market condition of the hotel sector in Central Lombok Regency. This study aims to analyze the property market conditions in the hotel sector in Central Lombok Regency by using the theory of six steps of property market analysis to get the conclusion that the property market conditions in the hotel sector in Central Lombok Regency are in an undersupply or oversupply state. This research is a quantitative study by calculating the level of demand and supply of hotel rooms in Central Lombok Regency based on historical data on the growth of the number of tourists and the number of hotel rooms in Central Lombok Regency.